Competencias socioemocionales en el aprendizaje de una segunda lengua en alumnado de educación primaria con dislexia = Abweichender Titel: Socio-emotional Competencies in Second Language Learning among Primary Education Students with Dyslexia - Gómara Lasarte, Verónica (Cauriensia, 2025)
Learning English as a foreign language poses specific challenges for students with dyslexia, particularly due to the language’s opaque orthography and the phonological and processing difficulties characteristic of this population. These challenges affect not only academic performance but also the socio-emotional domain, where foreign language anxiety, insecurity, and low self-esteem frequently emerge. The aim of this study was to analyse the perceptions of 19 Primary Education teachers regarding the socio-emotional experiences of students with dyslexia while learning English. A qualitative exploratory-descriptive design was employed through semi-structured interviews analysed with NVivo. Results show that most teachers identify persistent negative emotions, especially anxiety and emotional blocking during oral and reading tasks. Teachers also highlight the significant influence of methodology: active approaches (games, projects, drama, TPR) foster motivation and confidence, whereas traditional methods tend to increase pressure and discomfort. Positive emotions also emerged spontaneously, linked to supportive classroom environments and teacher scaffolding. The findings suggest that teachers play a crucial role in managing the emotional wellbeing of students with dyslexia and underscore the need for specific training in inclusive and emotional strategies to enhance access and participation in the English classroom.